Nanoencapsulation of Food-Grade Bioactive Compounds Using a Supercritical Fluid Extraction of Emulsions Process: Effect of Operational Variables on the Properties of Nanocapsules and New Perspectives - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Cerro-Munoz, D; Villegas-Vallejos, C (Academic Press, 2023)
In recent years, there has been a growing interest in the nanoencapsulation of a wide variety of bioactive compounds by extracting emulsions using Supercritical Fluid Extraction of Emulsions (SFEE) process for the development of nutraceutical products and functional foods. This work includes information of both the fundamentals and the stages of the SFEE process. It also describes the different equipment configurations used, such as spray, bubble column, or countercurrent columns operating in a batch process, semi-continuous, and/or continuous mode. In addition, this work also focuses on explaining the SFEE process effect on operational variables (emulsion composition, scCO2 pressure, temperature, scCO2 and emulsion flow rates, and process time) on the main physicochemical properties of the polymeric nanocapsules. Therefore, this work provides fundamental information and perspectives to contribute to the progress of the design of bioactive compound-loaded nanocapsules with the advantages of higher encapsulation efficiency, low organic residual solvents, and smaller size, as well as adapting to large-scale productions for the development of healthier and more bioavailable food products. © 2023